Perjuangan Perempuan dalam Dwilogi Novel Sekar Karya Muttaqwiati dan Iimpilkasinya dalam Pembelajaran Sastra di SMP - Badriyah, Badriyah (Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
This thesis in the result of research that expressed the fight of main character, a teenager in reacing her aspiration to continue to the higher education, beside that describe another character the support her to fight her aspiration. The method that used in this research is qualified method. The qualified research strategic method is analyzing that describe the data in this thesis in the form of teenage?s to fight her freedom to determine her fortune in learning fight not only done in big cities but also in small village. The research can be concluded that the fight women in dwilogi novel Sekar created by Muttaqwiati said that the writer is a women, capable to describe the effort of main character Sekar as village teenager that fight for her aspiration to continue to the higher education (high Scholl) beside that also describe?s fight. The implication in learning are in volving the role of students, contain vertical value, where adulth women can do the religion order freely. More over there are feminis value. The feminis value can be applicated on students in the form of respecting parents, have high learning aspiration, work, ethic, and high independence.